2021
DOI: 10.3389/fimmu.2021.656919
|View full text |Cite
|
Sign up to set email alerts
|

A Cytokine Network Balance Influences the Fate of Leishmania (Viannia) braziliensis Infection in a Cutaneous Leishmaniasis Hamster Model

Abstract: The golden hamster is a suitable model for studying cutaneous leishmaniasis (CL) due to Leishmania (Viannia) braziliensis. Immunopathological mechanisms are well established in the L. (L.) major-mouse model, in which IL-4 instructs a Th2 response towards progressive infection. In the present study, we evaluated the natural history of L. braziliensis infection from its first stages up to lesion establishment, with the aim of identifying immunological parameters associated with the disease outcome and parasitism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In addition, induction of a Th2 dominant response is responsible for pathogenesis in L. mexicana infection of mice 22 . A similar dominant Th2 response has been shown to play an important role in the pathogenesis of a related New World species, L. braziliensis , in a hamster model 23 . Therefore, it is necessary to develop vaccines that are effective at preventing infections with the New World Leishmania species.…”
Section: Introductionmentioning
confidence: 84%
“…In addition, induction of a Th2 dominant response is responsible for pathogenesis in L. mexicana infection of mice 22 . A similar dominant Th2 response has been shown to play an important role in the pathogenesis of a related New World species, L. braziliensis , in a hamster model 23 . Therefore, it is necessary to develop vaccines that are effective at preventing infections with the New World Leishmania species.…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, the local inflammation promoted by tattooing may contribute to the induction of an important immune response mediated by T cells, as observed in studies with DNA tattoo vaccines ( Platteel et al., 2017 ; Fotoran et al., 2020 ; Bakker et al., 2021 ). In studies of the hamster model infected with L. (V.) braziliensis carried out by Ribeiro-Romão and collaborators ( 2014 ) and Paiva and collaborators ( 2021 ), the lower parasite load generates a more benign course of infection, without systemic involvement and associated with the expression of a more balanced cytokine network. Therefore, terapeutic intervention in the early stages of infection, when the immune response is being mounted by the host, may favor the best outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that administering IFN-γ after P. aeruginosa challenge resulted in a significant decrease in macroscopic lung pathology changes ( 36 ). Recent literature suggests that IFN-γ gene expression is positively correlated with skin lesion size in hamsters infected with Leishmania braziliensis ( 37 ). The data reported above indicate that the tissue damage from microbial infection, especially lung damage, is associated with IFN-γ.…”
Section: Discussionmentioning
confidence: 99%